Planning Program for Gifted and Talented Students in Madrasa - Aprilis Saputri; Syafrimen Syafril; Yetri Yetri; Rorlinda Yusof (Yayasan Keluarga Guru Mandiri, 2024)
Madrasas support the development of gifted students by integrating general and religious education in a supportive environment. However, discrimination in education policies causes inequality and a lack of support for these students. Thus, special programs are essential for optimal development and career success. This research analyzes the planning of such programs in madrasas using a Systematic Literature Review. Data were collected from 34 documents from reputable scientific journals worldwide and analyzed using the Miles and Huberman interactive model. The findings reveal four key program components: (i) Identification of gifted students using assessment tools, expert teams, and multidimensional evaluation; (ii) Teacher training and professional development focusing on differential teaching strategies, collaborative learning, and partnerships with parents and stakeholders; (iii) Curriculum development including compression and enrichment; (iv) Development of special talents through artistic skills, academic competitions, creative skills, and collaborative activities. This research contributes to better educational policies and practices, ensuring gifted students receive the necessary support to reach their potential and succeed in their future careers.